Configurational crop heterogeneity increases within‐field plant diversity. Issue 4 (3rd March 2020) - Alignier, Audrey; Solé‐Senan, Xavier O.; Robleño, Irene; Baraibar, Bàrbara; Fahrig, Lenore; Giralt, David; Gross, Nicolas; Martin, Jean‐Louis; Recasens, Jordi; Sirami, Clélia; Siriwardena, Gavin; Bosem Baillod, Aliette; et al.
Abstract: Increasing landscape heterogeneity by restoring semi‐natural elements to reverse farmland biodiversity declines is not always economically feasible or acceptable to farmers due to competition for land. We hypothesized that increasing the heterogeneity of the crop mosaic itself, hereafter referred to as crop heterogeneity, can have beneficial effects on within‐field plant diversity. Using a unique multi‐country dataset from a cross‐continent collaborative project covering 1, 451 agricultural fields within 432 landscapes in Europe and Canada, we assessed the relative effects of compositional and configurational crop heterogeneity on within‐field plant diversity components. We also examined how these relationships were modulated by the position within the field. We found strong positive effects of configurational crop heterogeneity on within‐field plant alpha and gamma diversity in field interiors. These effects were as high as the effect of semi‐natural cover. In field borders, effects of crop heterogeneity were limited to alpha diversity. We suggest that a heterogeneous crop mosaic may overcome the high negative impact of management practices on plant diversity in field interiors, whereas in field borders, where plant diversity is already high, landscape effects are more limited. Synthesis and applications. Our study shows that increasing configurational crop heterogeneity is beneficial to within‐field plant diversity. It opens up a new effective and complementary way to promote farmland biodiversity without taking land out of agricultural production. We therefore recommend adopting manipulation of crop heterogeneity as a specific, effective management option in future policy measures, perhaps adding to agri‐environment schemes, to contribute to the conservation of farmland plant diversity. Abstract : Our study shows that increasing configurational crop heterogeneity is beneficial to within‐field plant diversity. It opens up a new effective and complementary way to promote farmland biodiversity without taking land out of agricultural production. We therefore recommend adopting manipulation of crop heterogeneity as a specific, effective management option in future policy measures, perhaps adding to agri‐environment schemes, to contribute to the conservation of farmland plant diversity. Editor's Choice Résumé: Accroître l'hétérogénéité du paysage en restaurant les éléments semi‐naturels pour enrayer le déclin de la biodiversité agricole n'est pas toujours économiquement faisable ou socialement acceptable pour les agriculteurs étant donné la compétition pour les terres. Nous faisons l'hypothèse qu'accroître l'hétérogénéité de la mosaïque de cultures, ci‐après désignée par l'hétérogénéité des cultures, peut aussi avoir des effets bénéfiques sur la diversité des plantes au sein des parcelles. Par l'utilisation d'un jeu de données multi‐pays issu d'un projet collaboratif trans‐continental rassemblant 1451 parcelles agricoles distribuées dans 432 paysages d'Europe et du Canada, nous avons estimé les effets de la composition et la configuration de l'hétérogénéité des cultures sur les composantes de la diversité des plantes au sein des parcelles. Nous avons mis en évidence un fort effet positif de l'hétérogénéité de configuration des cultures sur la diversité alpha et beta des plantes, à l'intérieur des parcelles. Ces effets sont aussi importants que l'effet des éléments semi‐naturels. Au niveau des bords de champs, l'effet de l'hétérogénéité des cultures se limite à la diversité alpha. Nous suggérons qu'une mosaïque de cultures hétérogène peut atténuer l'effet négatif des pratiques de gestion sur la diversité des plantes à l'intérieur des parcelles, tandis qu'au niveau des bords de champs, où la diversité en plantes est plus élevée, les effets du paysage sont plus limités. Synthèse et applications . Notre étude montre qu'accroître l'hétérogénéité de configuration des cultures est bénéfique pour la diversité des plantes au sein des parcelles. Elle ouvre de nouvelles perspectives quant au maintien et à la restauration de la biodiversité agricole sans empiéter sur les surfaces de production agricole. C'est pourquoi nous recommandons de considérer la manipulation de l'hétérogénéité des cultures dans l'élaboration des mesures politiques, en complément des mesures agri‐environnementales, pour contribuer à la conservation de la diversité des plantes en milieu agricole.